1983
DOI: 10.1300/j082v09n01_07
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Characteristics of Bisexual, Heterosexual and Homosexual Women

Abstract: One hundred and twenty-five female volunteers completed a questionnaire designed to measure masculinity, femininity, body cathexis, and self-esteem. Women were categorized as bisexual, heterosexual or homosexual according to self-labeling and according to erotic preference. The proportion of androgynous and undifferentiated individuals was much greater among self-labeled homosexual women. Feminine individuals were conspicuously under-represented among self-labeled homosexual and bisexual women. Women who repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Lesbians may, therefore, be at lower risk for body dissatisfaction that may lead to disordered eating. LaTorre and Wendenburg (1983) found that women who had had a sexual experience with another woman were more satisfied with their bodies and with themselves in general.…”
Section: Lesbiansmentioning
confidence: 96%
“…Lesbians may, therefore, be at lower risk for body dissatisfaction that may lead to disordered eating. LaTorre and Wendenburg (1983) found that women who had had a sexual experience with another woman were more satisfied with their bodies and with themselves in general.…”
Section: Lesbiansmentioning
confidence: 96%
“…Only two studies failed to find significant average differences, and in both cases, the differences still were in the predicted direction (Heilbrun & Thompson, 1977;Schlaich, 1976). Studies of female homosexuals and bisexuals, likewise, have found their mannerisms and interests, on average, to be more M/dF than among female heterosexuals (Heilbrun & Thompson, 1977;Kaye et al, 1967;LaTorre & Wendenburg, 1983;Oldham, Farnhill, & Ball, 1982;Spence & Helmreich, 1978;Thompson et al, 1973).…”
Section: Homosexuals Should Have Higher Frequencies Of Other Sexualmentioning
confidence: 99%
“…In a study noted previously, LaTorre and Wendenburg (1983) found that among self-labeled groups, masculine women were over-represented and feminine women under-represented among bisexuals. Among homosexuals, feminine and masculine women were under-represented while undifferentiated women were over-represented.…”
Section: Between Group Differencementioning
confidence: 83%